Roman Catholicism and modern science: a history - O'Leary, Don (Continuum, 2006)
From Galileo to Darwin -- Religion and science in Victorian Britain -- A church under siege -- Defensive strategies -- The suppression of the Mivartian hypothesis -- Antimodernism -- Catholicism and science in the interwar years -- Pope Pius XII and the new theology -- Science, faith, and the Second Vatican Council -- Pope John Paul II's philosophy of science and faith -- Bioethics -- Reflections